Cultural heritage — in politics, practice, and education (the example of Slovakia) - Koštialová, Katarína; Darulová, Jolana (Studia Etnologiczne i Antropologiczne, 2012)
Cultural and art heritage of Slovakia has been since 2007 one of the priorities in research and development. As a consequence of growing globalization and acculturation there is a real danger of the loss of traditional cultural values. That is why it is crucial to pay special attention to the research of cultural and art heritage. Application of knowledge on cultural heritage in the educational process is highly important because the level of national and ethnic identity and pride of young generation is not connected with cultural and art traditions of Slovakia.